2017
DOI: 10.1053/j.ajkd.2017.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ESRD and Mortality Associated With Change in Filtration Markers

Abstract: Background Using change in estimated glomerular filtration rate (eGFR) based on creatinine as a surrogate outcome in clinical trials of chronic kidney disease has been proposed. Risk of end-stage renal disease (ESRD) and all-cause mortality associated with change in other filtration markers has not been studied in chronic kidney disease populations. Study Design Observational analysis of two clinical trials Setting & Participants Participants in the MDRD (Modification of Diet in Renal Disease; n=317) Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…In line with our study, gradual increase in B2M levels across stages of CKD has been shown 38 . Furthermore, several associations between B2M levels and death, dialysis or cardiovascular events have been reported 39,42,43 , in agreement with our findings. 37 [n = 15 patients of CKD5 with haemodialysis (HD) were compared to n = 14 patients with stage 2-3 37 ] and LC-MRM-MS data [CKD stage 5 patients with HD (N = 24) versus CKD2-3].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with our study, gradual increase in B2M levels across stages of CKD has been shown 38 . Furthermore, several associations between B2M levels and death, dialysis or cardiovascular events have been reported 39,42,43 , in agreement with our findings. 37 [n = 15 patients of CKD5 with haemodialysis (HD) were compared to n = 14 patients with stage 2-3 37 ] and LC-MRM-MS data [CKD stage 5 patients with HD (N = 24) versus CKD2-3].…”
Section: Discussionsupporting
confidence: 93%
“…The selection of the specific markers was guided by the existence of mass spectrometry-based data for these proteins 37 , their expected abundance levels based on the existent literature, targeting to avoid extensive pre-fractionation, as well as levels of evidence for the association of these proteins with unfavorable outcome. Using the study by Glorieux et al 37 as a basis, involving high resolution LC-MS/MS analysis of plasma proteome from patients with CKD and reporting on associations to outcome, in combination to the aforementioned criteria, the tested panel includes B2M [38][39][40][41][42][43][44][45][46] and SERPINF1 [47][48][49][50] , having been largely studied in CKD and serving as positive controls for the approach, as well as AMBP, LYZ, HBB, and IGHA1 with some earlier reported associations 37 , nevertheless not been validated yet in association with disease progression via absolute quantification.…”
mentioning
confidence: 99%
“…One possible explanation why this was not the case might be that the development population of both equations were not the same: amongst others, the Inker (BTP) study population included individuals with a higher mean age and reported a diabetes prevalence of 21%, both of which corresponds more closely to the characteristics of our BIS population compared to the CKD-EPI study population. Also, one prominent non-GFR determinant in old age certainly is inflammation by which BTP is known to be less influenced compared to cystatin C 11 . This could be another possible explanation why the Inker (BTP) equation performed better than the combined creatinine/cystatin C- based equation.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to its renal metabolism, BTP has been shown to be freely filtered through the glomerular basement membrane with little if any tubular reabsorption or non-renal elimination 7 . Also, ß2-microglobulin (B2M), another low molecular weight protein, has been found to be highly correlated with measured GFR (mGFR) and like BTP, is less affected by age and sex 10 , 11 . Other research groups have investigated the approach of “biomarker-panels” using several, still unspecified, markers simultaneously, although these markers are not yet established for standard laboratory analysis 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, measurement of GFR in clinical practice is unpractical. Urine collection over 24 h with measurement of the excretion of SCr has been accepted as the best clinical approach to determine GFR [19]. However, one of the main requirements of GFR assessment is a steady state AKI stage that might often not be the case in rapidly evolving renal dysfunction [8].…”
Section: Renal Functional Reservementioning
confidence: 99%